Builders of images - Julia, Raul.; Vecchione, Judith; Mandelbaum, Juan.; WGBH (Television station : Boston, Mass.); Channel Four (Great Britain); Central Independent Television (South Burlington, VT : Annenberg/CPB Collection, 1993)
In this program, meet artists from Puerto Rico, Brazil, Mexico and Argentina who are creating works that reflect and influence their people's cultural identity.
Title on container: Builders of images: Latin American cultural identity.
In English, Spanish and Portuguese, with English subtitles and voiceovers.
VHS format.
Raul Julia, narrator.
Keywords: Latin American literature; Art, Latin American; Latin Americans -- Ethnic identity; Latin America -- Civilization